PROFIL FLAVOR ENHANCER HASIL HIDROLISIS ENZIMATIS IKAN BERNILAI EKONOMI RENDAH DALAM PENGGUNAANNYA SEBAGAI INGREDIEN PADA MAKANAN - Yuli Witono; Wiwik Siti Windrati; Iwan Taruna; Ardiyan Dwi Masahid; Alfindya Balgies Dardiri (JURNAL AGROTEKNOLOGI, 2017)
A natural flavor enhancer based on local source potential is indispensable. While the potential of inferior fishes of low economic value especially in the Madura archipelago, Indonesia such as tongue (‘lidah’), wedge (‘baji-baji’) and biblical (‘bibisan’) fish is very high and has not been utilized optimally. Fish raw materials can be developed as a hydrolyzate and derivatives thereof. In this case, the study aimed to find out the enzymatic hydrolysis enzymatic flavor enhancer profile of the inferior fishes with the comparison of inferior fish feedstock and additional ingredients has been performed. The study was conducted by observing descriptively the mean values of each parameter of 3 repetitions ie color, yield, moisture, ash, fat, protein, dissolved protein contentand maillard product and overall organoleptic value of flavor enhancer result of enzymatic hydrolysis process with 7 (seven) formulas of inferior fishes feedstock and additional ingredients (20:80, 40:60; 50:50; 60:40; 80:20; 90:10; 100: 0) and 9 (nine) types of additives according to the treatment. The results showed that inferior fishes flavor enhancers had a diversity of their profile values due to the comparison of fish and the weight of different additives. The greater the proportion of fish raw material to the additional ingredients, the higher the level of brightness, water, fat, protein, dissolved protein content and its maillard products, but the lower the ash content and the yield. The best inferior fish flavor enhancer profile based on sensory parameters resulted from formulations with 50 grams of inferior fish and 50 grams of additional ingredients. The treatment has a flavor enhancer profile with a brightness level of 69.90; yield of 45,17 gram, water content of 1,983%; ash content of 39.72%; 2.15% fat content; protein content of 24,17%, dissolved protein of 2,114 mg / ml; and maillard products of 0.17; as well as the overall value of organoleptic properties 2.88 (very dislike-rather like). Keywords: biduri enzyme, flavor enhancer, formulation, and inferior fishes